Proceedings of 5th International Conference on Advanced Manufacturing Engineering and Technologies NEWTECH 2017 - Majstorovic, Vidosav; Jakovljevic, Zivana; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents the proceedings from the 5th NEWTECH conference (Belgrade, Serbia, 5-9 June 2017), the latest in a series of high-level conferences that bring together experts from academia and industry in order to exchange knowledge, ideas, experiences, research results, and information in the field of manufacturing. The range of topics addressed is wide, including, for example, machine tool research and in-machine measurements, progress in CAD/CAM technologies, rapid prototyping and reverse engineering, nanomanufacturing, advanced material processing, functional and protective surfaces, and cyber-physical and reconfigurable manufacturing systems. The book will benefit readers by providing updates on key issues and recent progress in manufacturing engineering and technologies and will aid the transfer of valuable knowledge to the next generation of academics and practitioners. It will appeal to all who work or conduct research in this rapidly evolving field.
Machine tools -- CAD/CAM technologies -- Rapid prototyping and reverse engineering -- Nanomanufacturing -- New manufacturing technologies and advanced material processing -- Metrology and integrity of machined surfaces -- Manufacturing systems automation -- Cyber Physical Manufacturing Systems -- Monitoring and optimization of manufacturing processes -- Production planning and control -- Sustainable manufacturing systems development.
Keywords: Machinery; Manufactures; Machinery and Machine Elements; Machines, Tools, Processes